2010
DOI: 10.1177/1059840510372090
|View full text |Cite
|
Sign up to set email alerts
|

School Nurse Online Emergency Preparedness Training

Abstract: The objective of this study was to evaluate the effectiveness of a computer-assisted emergency preparedness course for school nurses. Participants from a convenience sample (52) of school nurses from New Mexico were randomly assigned to intervention or control groups in an experimental after-only posttest design. Intervention group participants completed 15 online emergency preparedness training modules followed by posttests, and control group participants completed the posttests without taking the training mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The evaluation of the young people's nutritional health training formulated the three discussed themes. The particular increase in the school nurses confidence was evident within the focus group which mirrors the link between training and confidence increase the literature evidenced (Atal, Patrick and Wang, 2016;Elgie et al, 2010;Jordan, Mackay and Woods, 2016). There was a feeling that the training 'reinforced' knowledge and therefore in turn increased the school nurses' confidence in practice (Crevacore, Jonas-Dwyer and Nicol, 2016;Crooks et al, 2005;Lundberg, 2008).…”
Section: Conclusion and Recommendationssupporting
confidence: 53%
“…The evaluation of the young people's nutritional health training formulated the three discussed themes. The particular increase in the school nurses confidence was evident within the focus group which mirrors the link between training and confidence increase the literature evidenced (Atal, Patrick and Wang, 2016;Elgie et al, 2010;Jordan, Mackay and Woods, 2016). There was a feeling that the training 'reinforced' knowledge and therefore in turn increased the school nurses' confidence in practice (Crevacore, Jonas-Dwyer and Nicol, 2016;Crooks et al, 2005;Lundberg, 2008).…”
Section: Conclusion and Recommendationssupporting
confidence: 53%
“…However, we identified sustainable strategies, which included incorporating the curricula into lesson plans that continued year-to-year (eg, math lessons, writing), acknowledging MA-CORD activities in performance evaluations, and schoolwide policies supporting messages taught during lessons (eg, no sugary drinks on campus). Additionally, online training modules are being considered as a low-cost way to train a school’s staff on health topics (28) and could be a way to overcome issues related to staff turnover. One study found no significant difference in adoption of an after-school nutrition and physical activity intervention when the staff were trained online versus face-to-face (29).…”
Section: Discussionmentioning
confidence: 99%
“…Elgie at al. [ 26 ] found that online training modules were a valuable resource for improving school nurses’ knowledge and skills regarding management of emergencies, but they might not affect participants' confidence. We observed that some nurses who knew first-aid procedures in the avulsion of permanent dentition did not feel confident enough to provide a tooth replantation.…”
Section: Discussionmentioning
confidence: 99%